Gestión financiera y su incidencia en la rentabilidad de la Farmacia Keyla, período 2018-2019 - Duche García, Verónica Janina (2021)
The current case study is based on an investigation carried out at the Keyla Pharmacy of the Caluma Canton, which has drawbacks in its profitability, so it was necessary to carry out a comparison of two years (2018-2019), in order to determine the causes of This problem, which establishes that in 2018 sales were lower than in 2019 but, on the contrary, higher profits were obtained than in 2019, it is clearly determined that there is a background for this to happen, so that the main causes are the Increase in sales costs, expenses, although these present a variation from one year to another and comparing it with the industry average does not turn out to be a problem of great magnitude for the entity, unlike the low inventory turnover, it is To say that said inventory remains on the shelf for a long time, causing an increase in the risk of obsolescence and giving way to maintenance expenses. To carry out this study, a financial analysis was taken into consideration; Applying both the vertical and horizontal analysis of its main accounts, in addition, financial ratios were also used that are of great help to be able to know in a more timely manner the shortcomings within an entity, despite the research method that was used was inductive, This method focuses first on the observation of facts, then on their analysis and finally the conclusion of the results, basically this is the method that allowed the present investigation to be concluded in a concrete way.